Motorcycle accidents: comparison between the years 1998 and 2010 in Londrina, Southern Brazil - Sant'Anna, Flavia Lopes; Andrade, Selma Maffei de; Sant'Anna, Flavio Henrique Muzzi; Liberatti, Christiane Lopes Barrancos (Revista de Saúde Pública, 2013)
OBJECTIVE: To compare the characteristics of motorcycle accidents and victims attended by pre-hospital care services. METHODS: A cross-sectional study was carried out using data on pre-hospital care of motorcyclists who had been injured in traffic accidents in Londrina, PR, Southeastern Brazil, in 2010, whose results were compared with those of a similar study conducted in 1998. Paramedic assistance registration forms were used as source of data. The fleets of motorcycles and the population of both years were used for estimating risks of accidents occurring. The Chi-square test was used to compare the profiles of accidents and victims. RESULTS: In 1998 and in 2010, respectively, 1,576 and 3,968 motorcyclists were seen (increase of 151.8%). The rate of injured motorcyclists per 1,000 inhabitants rose from 396.4 to 783.1, and that of the victims per 1,000 motorcycles from 53.1 to 61.1. Changes (p < 0.05) in the profile of accidents were observed, with higher proportions of falls from motorcycles, accidents between motorcyclists and occurrence during mornings, and a reduction of those at weekends. Regarding the victims, higher proportions of women, drivers, and those aged 35 years or over were observed. There was a decrease in the relative frequency of positive breathalyser results and an increase in the prevalence of helmet use. A lower proportion of victims were classified with moderate/severe coma and trauma scores and sent to hospitals. The immediate fatality rate dropped from 1.2% to 0.6%. CONCLUSIONS: Changes in the profiles of accidents and victims were observed in the period. Despite an absolute and relative increase in the number of victims of motorcycle accidents, a proportionally lower severity of these accidents was observed.